The Continental-Scale Greenhouse Gas Balance of Europe - Dolman, A. Johannes; Valentini, Riccardo; Freibauer, Annette; SpringerLink (Online service) (New York, NY : Springer New York, 2008)
The concentrations of CO2 and CH4 in the atmosphere are at the highest level they have been in the past 650,000 years. "The Continental-Scale Greenhouse Gas Balance of Europe", edited by A. Johannes Dolman, Annette Freibauer and Riccardo Valentini, highlights current results of research into the European greenhouse gases budget, including human-induced and biospheric sources and sinks. Much of this work is executed through the CarboEurope project, one of the world$1 (Bs foremost research programs on continental-scale carbon cycle research. The book assesses the current greenhouse gas (GHG) monitoring capabilities of Europe, identifies and quantifies the uncertainties involved, and outlines the direction of a continental-scale GHG monitoring network. The chapters provide a synthesis based on current research results of the European greenhouse gases budget, its sources and sinks and uniquely addresses both the methodology of carbon cycle science and the science itself. It aims to provide a synthesis of terrestrial carbon cycle science at the continental scale. At the same time both the individual chapters and concluding chapter outline the directions to and requirements for a pan-continental greenhouse gas monitoring network. The book provides the first comprehensive coverage of methodological and scientific aspects of a full GHG accounting and monitoring system.s
Introduction: Observing the Continental-Scale Greenhouse Gas Balance -- Observing a Vulnerable Carbon Cycle -- Assimilation and Network Design -- Quantifying Fossil Fuel CO2 over Europe -- Temporal and Spatial Distribution of Carbon Emissions -- Issues in Establishing In Situ Atmospheric Greenhouse Gas Monitoring Networks in Europe and in Regions of Interest to Europe -- Estimating Sources and Sinks of Methane: An Atmospheric View -- Designing an Observation Strategy for N2O -- Monitoring Carbon Stock Changes in European Soils: Process Understanding and Sampling Strategies -- Monitoring Carbon Stock Changes in European Forests Using Forest Inventory Data -- Flux Tower Sites, State of the Art, and Network Design -- Observations and Status of Peatland Greenhouse Gas Emissions in Europe -- Towards a Full Accounting of the Greenhouse Gas Balance of European Grasslands -- Regional Measurements and Modelling of Carbon Exchange -- Using Satellite Observations in Regional Scale Calculations of Carbon Exchange -- The Lateral Carbon Pump, and the European Carbon Balance -- Multiple Constraint Estimates of the European Carbon Balance -- A Roadmap for a Continental-Scale Greenhouse Gas Observing System in Europe.
Keywords: Environment; Climate change; Ecology; Environmental management; Environment; Environment, general; Ecology; Climate Change Management and Policy; Environmental Management; Climate Change; Electronic books